Macronyssus uncinatus - Orlova, Maria V.; Anisimov, Nikolay V. (Zenodo, 2023)
Macronyssus uncinatus (Canestrini, 1885) Distribution – Europe (as Macronyssus rhinolophi Radovsky 1967; as Macronyssus rhinolophi Estrada-Peña et al. 1989), Caucasus (Armenia) (as Macronyssus rhinolophi Ogadjanian and Arutyunian 1974), Azerbaijan (as Macronyssus rhinolophi Gadzhiev and Dubovchenko 1967), Uzbekistan (as Macronyssus rhinolophi Stanyukovich 1997), Tajikistan (as Macronyssus rhinolophi Stanyukovich & Malinovskiy 1992), Kyrgyzstan (as Macronyssus rhinolophi Rybin 1983). Africa (as Macronyssus rhinolophi Radovsky 1967). Hosts – Rhinolophus ferrumequinum (Dusbábek 1964; Radovsky 1967), R. clivosus (Radovsky 1967), R. hipposideros (Turk and Turk 1952), R. euryale (Dusbábek 1964; Estrada-Peña et al. 1989), R. mehelyi (Stanyukovich 1997), Myotis myotis (Radovsky 1967), My. blythi (Stanyukovich 1997), M. emarginatus (Dusbábek 1964; Estrada-Peña et al. 1989), Miniopterus schreibersii (Estrada-Peña et al. 1989), Pipistrellus pipistrellus (Dusbábek 1964). Published as part of Orlova, Maria V. & Anisimov, Nikolay V., 2023, Three new species of bat-parasitic gamasid mites of the genera Spinturnix, Macronyssus and Steatonyssus (Acari: Mesostigmata: Spinturnicidae, Macronyssidae) from Siberia and Mongolia, with keys to species of Russia and adjacent countries, pp. 211-239 in Persian Journal of Acarology 12 (2) on page 226, DOI:10.22073/pja.v12i2.76740, http://zenodo.org/record/8113590